3D Nanostructured Multielectrode Arrays: Fabrication, Electrochemical Characterization, and Evaluation of Cell–Electrode Adhesion. Issue 2 (8th November 2018) - Decker, Dominique; Hempelmann, Rolf; Natter, Harald; Pirrung, Melissa; Rabe, Holger; Schäfer, Karl Herbert; Saumer, Monika
Abstract: 3D nanostructures on top of planar multielectrode array (MEA) electrodes increase the surface area and can offer a tight and stable cell–electrode interface, thus leading to a crucial increase of the signal‐to‐noise ratio during measurement. However, each individual cell type might need specific dimensions and an arrangement of nanostructures that fits ideally to a specific cell type. Therefore, a fabrication method of 3D nanostructured MEA chips based on nanoimprint lithography, gold electroplating, and microstructuring techniques is presented which allows the fabrication of a whole set of MEA chips with different nanostructure layouts in one single approach. The chips are characterized using electrochemical methods, atomic force, and scanning electron microscopy. Furthermore, an impedance measurement method is presented to quantify cell–electrode adhesion of nanostructured and unstructured electrodes using the human embryonic kidney cell line (HEK 293). Double‐layer capacitance, transferred charge, and impedance values of different nanostructure layouts revealed a significant improvement compared to unstructured electrodes. The improvement strongly correlates with the increase of the electrochemical active surface area. Impedance measurement with impedance‐stable HEK 293 cells allows discriminating differences of cell adhesion between the individual nanostructure layouts. A significant increase or decrease of cell–electrode coupling depending on the nanostructure layout is demonstrated. Abstract : A variety of different 3D nanostructured multielectrode arrays can be fabricated simultaneously by combining nanoimprint lithography, electroplating, and microstructuring techniques. Double‐layer capacitance, charge transfer, and impedance are improved for nanostructured electrodes compared to unstructured electrodes. Additionally, cell culture experiments with human embryonic kidney (HEK) cells show a strong dependency on their adhesion for different nanostructure layouts.